Dark Mirror: Art from Latin America since 1968. - Beil, Ralf; Broeker, Holger; Borges, Jorge Luis, 1899-1986.; Suarez, Miranda (Kunstmuseum Wolfsburg : Bonn, 2015)
Alejo, Mauricio; Barrios, Alvaro; Bendedit, Luis, Fernando; Berliner, Edouardo; Camnitzer, Luis; Cardoso, Maria Fernanda; Caro, Antonio; Conlon, Donna; Costantino, Nicola; Cravo Neto, Maria; Dias, Antonio; Diaz, Gonzalo; Echevarria, Juan Manuel; Edeza, Ivan; Errazuriz, Paz; Ferrari, Leon; Francisco, René; Grippo, Victor; Jaar, Alfredo; Kuitca, Guillermo; Leirner, Nelson; Lopez, Marcos; Macchi, Jorge; Mendieta, Ana; Monge,¨Priscilla; Muniz, Vik; Munoz, Oscar, Ospina, Nadin; Pareja, Fernando; Pina, Manuel; Porter, Liliana; Restrepo, Jose Alejandro; Angel Rios, Miguel; Romero, Betsabee; Sandoval, Rosemberg; Serrano, Teresa; Smith, Melanie; Jaramillo, liliana Velze; Zabala, Horacio
Dark Mirror: Art from Latin America since 1968. Works from the Daros Latinamerica Collection, Kunstmuseum Wolfsburg, 26 september 2015- 31 januari 2016
boek